2008
DOI: 10.1126/science.1160769
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Mental Associations Predict Future Choices of Undecided Decision-Makers

Abstract: Common wisdom holds that choice decisions are based on conscious deliberations of the available information about choice options. On the basis of recent insights about unconscious influences on information processing, we tested whether automatic mental associations of undecided individuals bias future choices in a manner such that these choices reflect the evaluations implied by earlier automatic associations. With the use of a computer-based, speeded categorization task to assess automatic mental associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
210
8
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(237 citation statements)
references
References 17 publications
17
210
8
2
Order By: Relevance
“…The impact of conscious thought is thus likely to be seen only at the macro level, in temporally large units. Galdi, Arcuri, and Gawronski (2008) demonstrated this point nicely in a recent study. They asked participants to take a stance on a controversial issue after reading talking points from both sides of the debate.…”
Section: Conscious Thought Plays a Supporting Rolementioning
confidence: 65%
“…The impact of conscious thought is thus likely to be seen only at the macro level, in temporally large units. Galdi, Arcuri, and Gawronski (2008) demonstrated this point nicely in a recent study. They asked participants to take a stance on a controversial issue after reading talking points from both sides of the debate.…”
Section: Conscious Thought Plays a Supporting Rolementioning
confidence: 65%
“…Moreover, Fiedler and Bluemke (2005) demonstrated that it was possible to falsify the results of an IAT. Finally, concerning the difference in results on indecision, in this study, as in the studies by Friese et al (2012) or Galdi et al (2008), the undecided were the people who did not know who they would vote form, while in the study by Berthet et al (2015), the undecided were the people who voted for one of the other candidates in the first round, i.e. neither Hollande nor Sarkozy.…”
Section: Discussionmentioning
confidence: 99%
“…However, Galdi, Arcuri and Gawronski (2008) and Friese, Smith, Plischke, Bluemke and Nosek (2012) were able to demonstrate a difference in outcome between undecided voters and those who had already decided. For the undecided, implicit attitude is a better predictor of actual voting behavior than explicit attitude.…”
Section: Studymentioning
confidence: 99%
“…Research has begun to investigate neural activation that underlies the processing of political attitudes and preferences (Amodio et al, 2007;Zamboni et al, 2009), including studies on deliberative processing of political statements and simulated voting for political candidates (Westen et al, 2006;Spezio et al, 2008;Gozzi et al, 2010;Bruneau and Saxe, 2010;Rule et al, 2010).Yet the neural substrate underlying automatic processing of political preferences (Todorov et al, 2005;Ballew and Todorov, 2007;Berger et al, 2008;Galdi et al, 2008;Hassin et al, 2007;Carter et al, 2011;Healy et al, 2010) remains largely unstudied. Extending earlier fMRI studies, the present studyshowed that brain responses can reflect individual political preferences -for politicians and associated parties -in the absence of conscious deliberation and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid judgments of competence based solely on the facial appearance of candidates were shown to reliably predict the outcome of elections (Todorov et al, 2005;Ballew and Todorov, 2007). Moreover, implicit measures of attitudes that assessautomatic evaluative associations (Greenwald et al, 1998) were found to improve the prediction of supposedly deliberate behavior such as political voting (Karpinski et al, 2005;Friese et al, 2007;Galdi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%